2017
DOI: 10.1016/j.plefa.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with high-dose docosahexaenoic acid increases the Omega-3 Index more than high-dose eicosapentaenoic acid

Abstract: The increase in the O3I is greater with high dose DHA supplementation than with high dose EPA, which is consistent with the greater potency of DHA to modulate cardiometabolic risk factors. The extent to which such differences between EPA and DHA in increasing the O3I relates to long-term cardiovascular risk needs to be investigated in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 28 publications
5
37
0
Order By: Relevance
“…7,23 Regarding the EPA (20:5n-3), content between 90.2-162.1 mg g -1 were found in samples 1-11, except for sample 6, in which 120.2 mg g -1 was found; 273.0 and 440.3 mg g -1 were found in samples 12 and 13, respectively; in samples 14 and 15, which presented high levels of LA, 2.6 and 3.4 mg g -1 were found, respectively; EPA was N.D. in soybean oil. It was also observed for docosapentaenoic acid (DPA, 22:5n-3) fatty acid, for which content was found in the range of 12.9-23.2 mg g -1 in samples 1-11, except for sample 6 in which 15.9 mg g -1 was found; 39.8 mg g -1 was Allaire et al 2 reported that an increase of EPA + DHA in red blood cell membranes (O3I, omega-3 index) was observed with the consumption of supplements with high doses of DHA, compared with EPA, and O3I has already been associated with lower risk of coronary heart disease. It is important to note that, excluding sample 7, the analyzed samples (which were sources of EPA and DHA) were more concentrated in EPA than DHA.…”
Section: Fatty Acid Compositionmentioning
confidence: 77%
See 2 more Smart Citations
“…7,23 Regarding the EPA (20:5n-3), content between 90.2-162.1 mg g -1 were found in samples 1-11, except for sample 6, in which 120.2 mg g -1 was found; 273.0 and 440.3 mg g -1 were found in samples 12 and 13, respectively; in samples 14 and 15, which presented high levels of LA, 2.6 and 3.4 mg g -1 were found, respectively; EPA was N.D. in soybean oil. It was also observed for docosapentaenoic acid (DPA, 22:5n-3) fatty acid, for which content was found in the range of 12.9-23.2 mg g -1 in samples 1-11, except for sample 6 in which 15.9 mg g -1 was found; 39.8 mg g -1 was Allaire et al 2 reported that an increase of EPA + DHA in red blood cell membranes (O3I, omega-3 index) was observed with the consumption of supplements with high doses of DHA, compared with EPA, and O3I has already been associated with lower risk of coronary heart disease. It is important to note that, excluding sample 7, the analyzed samples (which were sources of EPA and DHA) were more concentrated in EPA than DHA.…”
Section: Fatty Acid Compositionmentioning
confidence: 77%
“…12 Therefore, 12 fatty acids were quantified in the lipid material present in capsules of omega-3 supplements (samples [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], and the results are presented in Table 2. Among them, samples 14 and 15 (both of Brazilian origin) were distinctive in composition compared to the other omega-3 supplements since they presented low levels of EPA and DHA, and high levels of linoleic acid (LA, 18:2n-6).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both Japanese and American take meat, egg, and fish, fish has far more omega-3 fatty acids compared to eggs. When we eat larger amounts of omega-3 fatty acids such as DHA and EPA, omega-3 fatty acids are known to replace omega-6 fatty acids in cell membrane [36]. The omega-3 fatty acids are found predominantly in oily fish, whereas arachidonic acid (the major long chain omega-6 fatty acid) is contained in meats and eggs and can be synthesized (albeit very slowly) [37].…”
Section: Discussionmentioning
confidence: 99%
“…In adipose tissue, EPA-supplemented groups exhibited a down-regulation of ADGRE1 (0 (49) . EPA promoted changes in extracellular matrix remodelling gene expression in adipose tissue (50) Allaire et al (51,52) and Vors et al v. EPA, P < 0•0001) (52) . EPA and DHA have similar effects on the expression of many inflammation-related genes in immune cells (53) ↓, Decrease.…”
Section: Obesity Treatmentmentioning
confidence: 98%